Immune Complexes Indirectly Suppress the Generation of Th17 Responses In Vivo. - Ceren Ciraci; John R Janczy; Nidhi Jain; Stefanie Haasken; Cyntia Pecli E Silva; Claudia F Benjamim; Jeffrey J Sadler; Alicia K Olivier; Yoichiro Iwakura; Dmitry M Shayakhmetov; Fayyaz S Sutterwala; Suzanne L Cassel (PLoS ONE)
The precise context in which the innate immune system is activated plays a pivotal role in the subsequent instruction of CD4+ T helper (Th) cell responses. Th1 responses are downregulated when antigen is encountered in the presence of antigen-IgG immune complexes. To assess if Th17 responses to antigen are subject to similar influences in the presence of immune complexes we utilized an inflammatory airway disease model in which immunization of mice with Complete Freund's Adjuvant (CFA) and ovalbumin (Ova) induces a powerful Ova-specific Th1 and Th17 response. Here we show that modification of that immunization with CFA to include IgG-Ova immune complexes results in the suppression of CFA-induced Th17 responses and a concurrent enhancement of Ova-specific Th2 responses. Furthermore, we show the mechanism by which these immune complexes suppress Th17 responses is through the enhancement of IL-10 production. In addition, the generation of Th17 responses following immunization with CFA and Ova were dependent on IL-1α but independent of NLRP3 inflammasome activation. Together these data represent a novel mechanism by which the generation of Th17 responses is regulated.